(untitled) (REGE Revista de Gestão, 2024)
Purpose – Patronage of local footwear have not been encouraging in Nigeria despite recent investments. The purpose of the study is to evaluate celebrity endorsement and customer patronage of SMEs (small-and medium-scale enterprises) products in African context, with focus on TEARS (Trustworthiness, Expertise, Attractiveness, Respect, and Similarity) model. Design/methodology/approach - The research was designed as a descriptive survey. An online structured questionnaire was applied for data collection. Cronbach Alpha and content validity were used for reliability and validity, respectively. TEARS model was used to ascertain key dimensions, and Pearson correlation coefficient and logistic regression were applied into the analysis. Findings - The findings reveal that celebrity endorsement is not associated with patronage of local footwears, though TEARS model analysis indicates the direction of consumers rating on celebrity endorsement. Factors such as recommendation and quality impact the consumer willingness to buy local footwear. Research limitations/implications – The small sample size calls for caution in generalization. Originality/value - The originality is buttressed from the value it provides for local product production and patronage. The significant factors are indicated as key to addressing low patronage.